Acceptance of internet banking services: The role of demographic factors as moderating variables - Ellen Theresia Sihotang; Dewi Murdiawati (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
Understanding the percentage of internet banking service usage, that is inferior to the percentage of mobile banking usage, has been important to observe factors affecting behavioral intention to use internet banking. The purpose of this study is to analyze the determinants of internet banking usage by applying demographics as a moderator of intentional behavior to design the internet banking marketing strategies based on customer needs and wants. This study employs a judgment sampling technique with a sample size of 282 respondents processed by SPSS 23 and WarpPLS 6.0. The factors affecting the use of internet banking services are perceived usefulness, perceived ease of use, as well as perceived security and privacy. However, demographic elements variables (gender, age and education level) are the moderation of perceived security and privacy on behavioral intentions in using internet banking. In addition, men are more focus to on security and privacy than women. Moreover, older people are more concern withconsidering security and privacy more than younger people. Undergraduate/postgraduate and non-graduate people consider safety and privacy. The implication of this study is to improve the security system and determine the target market of internet banking by considering demographic elements factors as athe strategy to maintain and toas well as increase the use of internet banking.